ANALISIS PENDAPATAN DAN KELAYAKAN USAHATANI CABAI RAWIT DI DESA SUNJU KECAMATAN MARAWOLA KABUPATEN SIGI - Agnes, Anita; Antara, Made (AGROTEKBIS, 2017)
Sunju is one of villagesin Marawola district thathas a great cayenne production.  However, the production has not yet created sufficient income for its farmers.  This condition led to this researchaiming to determine the income and  the feasibility of the cayenne farming system in Sunju village. The research was conducted in May to June 2015.  The research location was purposively selected considering that Sunju is an area that has high cayenne productivity (8 t/ha). A number of30 respondentswere selected from 43 household head farmers using a Simple Random technique.  Data was analyzed using income and feasibility analysis.  The average income of the farmers for one planting season was found to be IDR 8,021,500.00 and the Revenue of Cost Ratio was 2.69 indicating that the cayenne farming system is feasible. Keywords: Cayenne, Expedience, Farming, and Income.